Imaging sports lesions of the groin - van Dyck, P.; Gielen, J. L.; Vanhoenacker, F. M.; Parizel, P. M. (Medicine and Science in Tennis, 2007)
Most athletes with groin pain attend an imaging department if symptoms persist. Therefore, most patients referred by the clinician for further imaging evaluation present with chronic groin injury. In daily radiological practice, acute groin injury is rare. Differential diagnosis of groin pain is broad and clinical diagnosis of groin lesions may be confusing, reflecting the fact that the causes of groin pain are protean. Moreover, combined pathology is often present in chronic groin pain and these different groin conditions are often interlinked. Medical imaging may play a crucial role to narrow differential diagnosis and to display better the interlinked nature of different groin conditions.